Multistage Nanoparticles for Improved Delivery into Tumor Tissue - Stylianopoulos, Triantafyllos (2012)
The enhanced permeability and retention (EPR) effect has been a key rationale for the development of nanoscale carriers to solid tumors. As a consequence of EPR, nanotherapeutics are expected to improve drug and detection probe delivery, have less adverse effects than conventional chemotherapy, and thus result in improved detection and treatment of tumors. Physiological barriers posed by the abnormal tumor microenvironment, however, can hinder the homogeneous delivery of nanomedicine in amounts sufficient to eradicate cancer. To effectively enhance the therapeutic outcome of cancer patients by nanotherapeutics, we have to find ways to overcome these barriers. One possibility is to exploit the abnormal tumor microenvironment for selective and improved delivery of therapeutic agents to tumors. Recently, we proposed a multistage nanoparticle delivery system as a potential means to enable uniform delivery throughout the tumor and improve the efficacy of anticancer therapy. Here, we describe the synthesis of a novel multistage nanoparticle formulation that shrinks in size once it enters the tumor interstitial space to optimize the delivery to tumors as well as within tumors. Finally, we provide detailed experimental methods for the characterization of such nanoparticles.